MO071: Hemolysis is Associated with Altered Heparan Sulfate of Endothelial Glycocalyx And with Local Complement Activation in Thrombotic Microangiopathies. (3rd May 2022) - Laboux, Timothée; Maanaoui, Mehdi; Allain, Fabrice; Gibier, Jean-Baptiste; Lopez, Benjamin; Denys, Agnes; Grolaux, Gaelle; Lebas, Celine; Provôt, François; Lancel, Steve; Hazzan, Marc; Boulanger, Eric; et al.
Abstract: BACKGROUND AND AIMS: The complement system plays a key role in the pathophysiology of renal thrombotic microangiopathies (TMA), as illustrated by atypical hemolytic uremic syndrome (HUS) characterized by a high rate of mutations in complement proteins. However, complement abnormalities are not fully sufficient to drive to TMA lesions. Among other suspected pathophysiological actors, we hypothesize that the alteration of heparan sulfate (HS) of endothelial glycocalyx—a cell membrane glycoaminoglycans and glycoproteins matrix able of regulating complement by binding factor H—may play a significant role. METHOD: We recorded clinical and histological features in native kidney biopsies from a monocentric retrospective cohort of 72 TMA-patients. Glomerular HS integrity and local complement activation markers (C3 and C5b9 staining) were analyzed by immunofluorescence (IF) and immunohistochemistry. Using an in vitro endothelial cells model (human umbilical vein endothelial cells, HUVECs), we studied the impact of heme exposure (30', 37°C)—a major product of hemolysis—on endothelial HS integrity by IF and flow cytometry (FCM). Heme-induced HS disruption was studied by slot blot of HS core-protein Syndecan (SDC) 1 and 4 in cells supernatant. Artificial enzymatic degradation of HS was achieved after exposure of HUVECs to a combination of heparinases I, II and III (30', 37°C), and we studied its effect on the ability of the HS-free cell membrane to locally activate complement by analyzing C3b deposition by IF and FCM, and the release of complement anaphylatoxins C3a and soluble attack complex membrane s-C5b9 in the cell supernatants by ELISA. The HS remodeling process induced by heme exposure (16 h, 37°C) were indirectly analyzed via a transcriptional profiling of the expression of the key enzymes involved in HS synthesis by RT–qPCR. RESULTS: Glomerular HS staining decreased in 57 TMA-patients (79%), moderately (2+) or strongly (0–1+) in 20 (28%) and 37 (51%) cases, respectively. Reduced HS density was significantly associated with hemolysis at the time of biopsy (P = 0.008) and local complement activation (C3d and/or C5b-9 deposits, P < 0.001). Hemolysis at the time of biopsy was associated with more severe glomerular TMA lesions (P = 0.025), the presence of vascular thrombi (P = 0.007) and local complement activation (C3d and/or C5b-9 deposits, P = 0.006). On endothelial cells (HUVECs), we confirmed that HS expression was decreased after heme exposure in IF and FCM (P < 0.01). Coherently, HS core-proteins SDC-1 and 4 were significantly increased in HUVECs supernatant (P < 0.05), suggesting a negative heme-driven impact on HS integrity. Artificial HS degradation increased C3b membrane deposition on HUVECs on average ∼ 3 fold by FCM and ∼ 10 by IF, and we observed an increased release of complement C3a and s-C5b9 in cells supernatant (P < 0.05). Finally, we showed that prolonged exposure to heme induced a decreased of genic expression of C5-Epimerase and an increase in 6-OST1 and 3-OST1 expression (P < 0.05), the very three crucial genes of HS remodeling specifically and sequentially involved in the generation of anti-thrombin pattern, the well-known key regulator of the HS/heparin-driven inhibition of coagulation. CONCLUSION: This study highlights the impact of hemolysis on the integrity of endothelial glycocalyx HS, both in kidney biopsy of TMA-patients and in an in vitro endothelial cell model, and suggests that acute alteration of HS is a mechanism of heme-induced complement activation. The endothelial glycocalyx appears then to be an important key in the understanding of TMA and could lead to the development of therapeutics targeting its preservation and/or reconstitution, in order to better control the disease.